2016
DOI: 10.1038/srep35053
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation and Imaging Properties of Gadolinium-Based Nanoparticles in nonhuman primates

Abstract: In this article, we report the safety evaluation of gadolinium-based nanoparticles in nonhuman primates (NHP) in the context of magnetic resonance imaging (MRI) studies in atherosclerosis bearing animals and healthy controls. In healthy NHP, the pharmacokinetics and toxicity profiles demonstrated the absence of dose, time, and sex-effects, as well as a suitable tolerance of intravenous administration of the nanoparticles. We investigated their imaging properties for arterial plaque imaging in a standard diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In addition to its application as a positive MRI T 1 contrast agent 69 , gadolinium-based nanoparticles (GdNPs) have been identified as valuable theranostic sensitizers for radiation therapy 70 , 71 ( Table 1 ). More importantly, GdNPs, such as AGuIX (Activation and Guidance of Irradiation by X-ray) 87 , exhibit diminished or no toxicity in preclinical studies employing mice and monkeys and are eliminated rapidly via the kidneys 88 , 89 . In contrast, the release of free Gd (III) from acyclic chelates constituting commonly used conventional Gd-based MRI contrast agents in the acidic conditions of the kidneys can be responsible for the high frequency of serious and sometimes fatal nephrogenic systemic fibrosis (NSF) observed in patients with renal failure.…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…In addition to its application as a positive MRI T 1 contrast agent 69 , gadolinium-based nanoparticles (GdNPs) have been identified as valuable theranostic sensitizers for radiation therapy 70 , 71 ( Table 1 ). More importantly, GdNPs, such as AGuIX (Activation and Guidance of Irradiation by X-ray) 87 , exhibit diminished or no toxicity in preclinical studies employing mice and monkeys and are eliminated rapidly via the kidneys 88 , 89 . In contrast, the release of free Gd (III) from acyclic chelates constituting commonly used conventional Gd-based MRI contrast agents in the acidic conditions of the kidneys can be responsible for the high frequency of serious and sometimes fatal nephrogenic systemic fibrosis (NSF) observed in patients with renal failure.…”
Section: Metal-based Nanoenhancers For Ionizing Ramentioning
confidence: 99%
“…In vivo experiments were performed to determine the maximum tolerated doses (MTD) of AGuIX ® in mammalians. MTDs of 450 mg/kg [20] in rodents and 750 mg/kg [21] in Cynomolgus monkeys were respectively found. During a phase Ib clinical trial (NanoRAD [9]), AGuIX ® was administered up to the dose of 100 mg/kg to patients, which corresponds to the recommended dose for phase 2 multicentric clinical trials (NCT03818386 and NCT02820454) [9,18] with 3 injections at 100 mg/kg at different times during radiotherapy treatment.…”
Section: Introductionmentioning
confidence: 95%
“…A ligand matching both criteria was a DOTA derivative, DOTAGA (GA for glutamic acid) . Reassuringly, studies have demonstrated the robust nature of Gd(III) complexes formed with this ligand, and no significant toxicity has been observed, even with compounds presenting multiple metal complexes …”
Section: Resultsmentioning
confidence: 98%